ANALISIS KEBANGKRUTAN MENGGUNAKAN RASIO ALTMAN Z-SCORE - Nuurillah, Nisaa’; Ardiansari, Anindya (Management Analysis Journal, 2015)
This research purposed in order to find out bankruptcy indication of listed in LQ-45 index and delisted companies in Indonesian Stock Exchange using Altman Z-Score. Research population are all listed and delisiting companies in Indonesian Stock Exchange, sample was chosen based on purposive sampling criteria. Among 23 sample companies in LQ45, there are 3 companies predicted as grey area in three years and there is a company predicted as grey area in one year and then predicted on bankrupt condition in the next two years. There are one company which predicted as bankrupt condition in three years. From 10 sample companies which was delisted from IDX, there is one company which predicted as healthy condition in two years, then predicted as bankrupt in the next year. There is a company which was predicted as grey area in one year. This case can be proven that Altman Z-Score ratio has high accuracy in bankruptcy prediction